Pengaruh Latihan Skipping Dan Barrier Hops terhadap Peningkatan Vertikal Jump Pada Pemain Tim Putra Di PBV Pendeta - Sapraji, Sapraji; Basri, Muhammad Hasan; Rahman, Taufik (Physical Education Departement of University PGRI Jombang, 2024)
This study aims to analyze the effect of skipping and barrier hops training on increasing vertical jump in male players at PBV. Pastor. The type of research conducted using an experiment with two different groups by providing training programs to the two groups with different treatments, namely group A Barrier Hop training and group B Skipping training. Data were analyzed using a different sample t test. The results of the study showed that the group of men's volleyball team players at PBV. Pastor who were given skipping training obtained t count = 1.695> t table 1.83 (0.05: 9), which means there is no significant effect on increasing vertical jump in men's volleyball team players at PBV. Pendeta after participating in skipping training for 2 months. While for the group of men's volleyball team players at PBV. The Pendeta who was given barrier hops training obtained t count = 1.983 > t table 1.83 (0.05:9) indicating that there was a significant influence on increasing the vertical jump in the men's volleyball team players of PBV.Pendeta Sumenep after participating in barrier hops training for 2 months.